Depression Symptoms, Risk Behaviors, Somatization and Social Support Within Two Different Microsystems of Early Adolescents - Renata Sikora (Seminare, 2024)
The main aim of the study was to find out if early adolescents who attend two different school microsystems i.e. division of high educational outcomes and division of low educational outcomes differ in terms of depression symptoms, somatization, risk behaviors, school stress and the perception of teachers’ social support which they receive at school. There were 60 adolescents who took part in the study. The set of five tools was applied as follows: Children Depression Inventory CDI-2 (Kovacs 2014), Children Somatization Inventory – short (Walker et al. 2009), Children and Adolescent Social Support Scale – a subscale ‘teachers support’ (Malecki et al. 1999), List of Risk Behaviors in Late Childhood and Early Adolescence (Sikora 2016) and a list of school stressors which was created by participants. The results show the medium level of depression symptoms in a whole group and high level of symptoms in girls who attend low outcomes division. The level of somatization is also the highest among girls of low outcomes division. Risk behaviors are declared more often by students of high outcomes division. Social support was viewed differently in two divisions. The teachers’ help was connected to the well-being of students and provided protection against the mental costs of being at school. Study results call for closer attention to be put on the school context of early adolescents. The intervention and prevention programs should consider some cultural changes in risk behaviors and in symptoms of somatization declared by early adolescents in the study